DIEP Flap Breast Reconstruction Complication Rate in Previously Irradiated Internal Mammary Nodes - Shechter, Shirley; Arad, Ehud; Inbal, Amir; Friedman, Or; Gur, Eyal; Barnea, Yoav (Journal of Reconstructive Microsurgery, 2018)
Background Postmastectomy radiation therapy (PMRT) is a widely accepted treatment for locally advanced breast cancer. Some patients require additional boost radiation to the internal mammary nodes as the part of regional nodal irradiation (RNI). Delayed breast reconstruction with an autologous free flap using the internal mammary vessels for microvascular flap anastomosis is a common practice for these patients. The aim of our study was to evaluate the effect of RNI on autologous microvascular breast reconstruction.Patients and Methods A retrospective study was performed on 57 patients (69 flaps) undergoing deep inferior epigastric perforator (DIEP) flap for delayed breast reconstruction after radiation therapy. The study group included 37 patients (65%) who received PMRT and RNI to the internal mammary nodes. The control group included 20 patients (35%) who received PMRT alone. Early and delayed surgical complications, including wound complications, fat necrosis, and flap loss, were compared between the groups.Results The patient demographics in both groups were similar. Complication rate showed a higher trend in the study group for flap loss (8.3% versus 0%) and vascular anastomosis failure (5.6% versus 0%), but with no statistical difference (p = 0.54, 0.53, respectively). The control group showed a higher trend in fat necrosis (25% versus 8.3%, p = 0.11).Conclusions DIEP flap breast reconstructions with internal mammary vessels anastomosis should be performed with cautious in patients who had received RNI to internal mammary nodes because of potential added risk for surgical complications.
Keywords: internal mammary nodes; irradiation; DIEP flap breast reconstruction